Normal Index 1887-03 (March 1887) - San Jose State Normal School :::Creator::::::::::::; Wilson, David A.:::Editor::::::::::::
Volume 2, number 8. The Normal Index was a monthly publication of the Senior Classes of the San José State Normal School. Submissions were accepted from current students and alumni. In addition to editorials and articles, obituaries and alumni notes were also featured. From vol. 1, no. 3 (Dec. 1885) to vol. 3, no. 6 (Feb. 1888), a section of the Index was devoted to the California State Normal School branch at Los Angeles. Edited by its own students, the Los Angeles section featured editorials, activities, and alumni news of the institution that later became UCLA.